A case of Brugada Syndrome unmasked by a postoperative febrile state - Jharendra Rijal; Smith Giri; Sumesh Khanal; Khagendra Dahal (Caspian Journal of Internal Medicine, 2015)
Abstract Background: Brugada Syndrome (BS) is an inherited ion channelopathy characterized by an electrocardiographic (ECG) pattern of a coved type ST segment elevation in right precordial leads with or without right bundle branch block. Case Presentation: A 23-year old male presented with right lower quadrant abdominal pain. Further evaluation revealed a diagnosis of acute appendicitis. The patient developed a febrile episode on second post-operative day of laparoscopic appendectomy. ECG revealed features consistent with BS. Prompt control of temperature in the patient resolved the ST-segment elevation and prevented potentially life-threatening arrhythmias. Conclusion: Febrile episodes in susceptible patients may unmask a concealed BS. Prompt control of temperature is advocated to reduce the risk of life-threatening arrythmias